Problem of moral education of preschool children: theoretical aspect (Pedagogy of Higher and Secondary Education, 2015)
Knyazheva I. A. Problem of moral education of preschool children: theoretical aspect.In the article theoretical bases of the problem of moral education of preschool children were analysed, basic directions of scientific researches on issue of moral education of under-fives were selected, the features of normative and person centered approaches in the work of educators of preschool educational institutions were described.
Keywords: moral education; preschool age children; normative approach; personal based approach; educators; preschool educational institutions